Pendampingan Anak-Anak dalam Mendeteksi Perubahan Perilaku Akibat Trauma Bom Teroris di Rusunawa Wonocolo Sidoarjo - Wiwin Ainis Rohtih; M. Mukhid Mashuri (LPPM Universitas Yudharta Pasuruan, 2019)
there was a deep trauma in the minds of people, this can be seen in psychological problems, especially children. The psychological trauma can result in depression and anxienty disorders, at a more severe level can lead to post traumatic stress disorder (PTSD). The lack of knowledge and skills of parents makes this problem reguires an active role from various parties, one of the by providing assistance to detect behavioral changes that occur in children. This Assistance uses the Participatory Action Research (PAR) method, with the formulation of stategies: personal approach, community approach, and collaboration with relevant institutions and psychology consultants with capacity building. The results of this community service program have been able to increase awareness, care, and the abilty of parents, teachers of religious institutions in traumatic child care. In addition, solidarity was formed between citizens and also religious institutions for children victims of terrorist bombings. Efforts to strengthen the role of the family will become a new movement in the Rusunawa Wonocolo area in taking part responsibly for social problems that accur, especially assistance for children who are traumatized.